2017
DOI: 10.1089/ten.teb.2016.0455
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Cell-Based Strategies for Soft Tissue Reconstruction

Abstract: Soft tissue reconstruction to restore volume to damaged or deficient tissue beneath the skin remains a challenging endeavor. Current techniques are centered around autologous fat transfer, or the use of synthetic substitutes, however, a great deal of scientific inquiry has been made into both the molecular mechanisms involved in, and limitations of, de novo adipogenesis, that is, the formation of new adipose tissue from precursor cells. To best comprehend these mechanisms, an understanding of defined markers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 121 publications
0
48
0
Order By: Relevance
“…Generating IMF in-vitro may require intensive research, as current adipose tissue engineering research focuses on fat outside the muscle (Hong et al, 2005;Gomillion and Burg, 2006;Brett et al, 2017) and uses human and mouse models, which protocols are inefficient for ruminant animals (Laliotis et al, 2010;Ma et al, 2018). Research on adipose tissue vascularization using matured ECs and MSCs, revealed a synergetic effect between angiogenesis and adipogenesis (Kang et al, 2009;Wittmann et al, 2015;Volz et al, 2016).…”
Section: Adipocytes and Imfmentioning
confidence: 99%
“…Generating IMF in-vitro may require intensive research, as current adipose tissue engineering research focuses on fat outside the muscle (Hong et al, 2005;Gomillion and Burg, 2006;Brett et al, 2017) and uses human and mouse models, which protocols are inefficient for ruminant animals (Laliotis et al, 2010;Ma et al, 2018). Research on adipose tissue vascularization using matured ECs and MSCs, revealed a synergetic effect between angiogenesis and adipogenesis (Kang et al, 2009;Wittmann et al, 2015;Volz et al, 2016).…”
Section: Adipocytes and Imfmentioning
confidence: 99%
“…Adipose tissue engineering aims to provide alternatives to current reconstructive procedures . Adipose‐derived stromal cells (ASCs) are easily accessible through liposuction procedures and have been widely employed in tissue engineering approaches.…”
Section: Mew Parameters and Corresponding Scaffold Dimensions Determimentioning
confidence: 99%
“…This review aims to assess recent advances in 3D modeling for diseases centered on adipose tissue such as: obesity, type 2 diabetes, and cancer adjacent to adipocytes. Although 3D adipose models are also used for soft tissue reconstruction after physical trauma or tumor resections, these topics are outside the scope of disease-based models covered in this review, but are thoroughly reviewed elsewhere [6][7][8].…”
Section: Introductionmentioning
confidence: 99%